Policies tackling the "web of constraints" on resource efficient practices: the case of mobility. Issue 1 (1st January 2019) - Dijk, Marc; Backhaus, Julia; Wieser, Harald; Kemp, René
Abstract: In practice, environmental policy is only moving slowly from a focus on promoting environmental technologies to a focus on greening socio-technical systems. Policy measures to stimulate resource efficiency (RE) typically address the national, sectoral, or company level. This article shows how an analysis addressing practices that citizens engage in, such as eating or mobility, can contribute to more effective RE policy. It is instrumental to highlight policy contradictions in the current mix of policies and offer suggestions for stronger policy synergies. We offer a conceptual and empirical analysis based on the results of a large-scale survey (1200+ respondents) in three countries (Austria, Hungary, and The Netherlands), focusing on one of the most resource intensive consumption domains: mobility. We apply a framework that includes the social context of resource consumption, addressing how practices that citizens engage in are shaped by both "collective" physical infrastructures, the business models of products, social meanings, and regulatory incentives, and also by "individual" knowledge and skills, values, and financial capabilities. Our "web of constraints" perspective on RE highlights the interrelatedness of individual actor and collective factors. It is instrumental for an integrative policy discussion, addressing a range of factors hindering RE, anticipating policy contradictions, to capitalize on synergies.